2009
DOI: 10.1002/anie.200805703
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Double‐Michael‐Addition/Cyclization/Acyl Migration of 1,4‐Dien‐3‐ones and Ethyl Isocyanoacetate: Stereoselective Synthesis of Pyrrolizidines

Abstract: Up to four adjacent stereocenters can be formed stereoselectively in the construction of a pyrrolizidine unit through a novel organocatalytic reaction that involves treatment of various dienones with ethyl isocyanoacetate (see scheme; DBU = 1,8-diazabicyclo[5.4.0]undec-7-ene). Mechanisms for this atom-economic, one-pot synthesis have been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 141 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Preliminary results revealed that a wide range of CF 3 -containing oxazolines, imidazolines, and pyrrolines were conveniently constructed by formal [3 + 2] cycloaddition of α-trifluoromethylated methyl isocyanides with polar multiple bonds . In continuation of our studies on isocyanide-based annulation reactions, we report herein a unique and unprecedented chemoselective double annulation of α-trifluoromethylated methyl isocyanides with o -acylaryl isocyanides for the efficient synthesis of trifluoromethylated oxadiazino­[3,2- a ]­indoles with complete atom-economy (Scheme , eq 4). In this domino reaction, new reactivity profiles are disclosed, including isocyanide formal insertion into the CO bond and chemoselective heterodimerization of two different isocyanides.…”
mentioning
confidence: 78%
“…Preliminary results revealed that a wide range of CF 3 -containing oxazolines, imidazolines, and pyrrolines were conveniently constructed by formal [3 + 2] cycloaddition of α-trifluoromethylated methyl isocyanides with polar multiple bonds . In continuation of our studies on isocyanide-based annulation reactions, we report herein a unique and unprecedented chemoselective double annulation of α-trifluoromethylated methyl isocyanides with o -acylaryl isocyanides for the efficient synthesis of trifluoromethylated oxadiazino­[3,2- a ]­indoles with complete atom-economy (Scheme , eq 4). In this domino reaction, new reactivity profiles are disclosed, including isocyanide formal insertion into the CO bond and chemoselective heterodimerization of two different isocyanides.…”
mentioning
confidence: 78%
“…On the basis of above observations and the related work, [16][17][18][19]21] a possible pathway for this domino reaction is proposed in Scheme 5. The tandem cyclization-annulation may involve the following domino sequence: Michael addition of isocyanides 2 to 2methyleneaminochalcone 1 under basic conditions provides the anion I; [21] proton shift takes place to generate anion II, followed by intramolecular Mannich reaction to form the bicyclic nitrogen anion III (this step may be reversible based on the results of eq 6 in Scheme 4); sequential proton shift and cyclization give the tricyclic intermediate V, which undergoes 1,3-proton shift to produce tetrahydropyrroloquinolines 4 (EWG = CO 2 Et) or intermediate VI (EWG = Ts).…”
mentioning
confidence: 87%
“…[15] In recent years, our research efforts have been devoted to the domino transformation of functionalized isocyanides. [16,17] Accordingly, a range of structurally complex heterocycles, including pyrrolizidines, [ were efficiently constructed from the domino reaction of a-acidic isocyanides with all-carbon 1,4-, 1,5-or 1,7dielectrophiles (Scheme 1, top). In continuation of our studies on isocyanide-based reactions, [18] as well as inspired by Xu's work [19] wherein 2-methyleneaminochalcones were used as aza-dielectrophiles, we herein report the tandem cyclization-annulation of a-acidic isocyanides with 2-methyleneaminochalcones for the straightforward and efficient synthesis of 3H-pyrrolo [2,3-c]quinolines and tetrahydro-3H-pyrrolo[2,3-c]quinolines, respectively (Scheme 1, bottom).…”
mentioning
confidence: 99%
“…It is desirable to develop a new strategy for the efficient construction of the azabicyclic skeleton from simple acyclic starting materials in a single step. 8 An organocatalytic domino reaction of 1,4-dien-3-ones with ethyl isocyanoacetate that allowed the formation of three C-C and one C-N bonds in a regio-and diastereoselective manner in a single reaction were used to synthesize a series of novel PA-1. PA-1, which showed strong antibacterial activity, was used to systematically study the antibacterial mechanism of PA-1 derivatives, providing a novel antibacterial drug candidate.…”
Section: Introductionmentioning
confidence: 99%